SATISFACTION AND LOYALTY IMPROVEMENT MODEL ON THE QUALITY OF HIGHER EDUCATION SERVICES - Munizu, Musra; Hamid, Nurdjanah (Jurnal Dinamika Manajemen, 2015)
This study analyzes the influences of studentsâ perceptions about the quality of higher education services to satisfaction; high quality of education services to the loyalty; and student satisfaction to the loyalty on private universities (PTS) in Makassar. The population used in this study was all students of economics faculty that have been studied over four semesters at big four PTS in Makassar. The sampling method used in this study was simple random sampling. The number of samples is 114 people. Both Descriptive Statistics and Structural Equation Modelling (SEM) were used as method of analysis. The data processed by using IBM SPSS and AMOS 20. The result shows that the quality of higher education services significantly influence student satisfaction, the quality of higher education services significantly influence student loyalty, and student satisfaction significantly influences student loyalty. Loyalty is more determined by student satisfaction rather than the quality of higher education services.